2018
DOI: 10.1016/j.foodhyd.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and salts on microstructure and viscoelastic properties of lemon peel acid insoluble fiber suspensions upon high pressure homogenization

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The washing solvents also showed a significant impact on the rheological parameters ( G ′ and G ′′), where washing with just water (CFS1) showed lower values as compared to a mixture of water and alcohol (CFS4). This indicates that a mixture of water and alcohol significantly decreases the insoluble components of both water and alcohol from the citrus fibres resulting in higher G ′ and G ′′ values as compared to washing with just water (similar behaviour was observed with the reduced pectin content via washing by Viuda-Martos et al (2012) 28 and Willemsen et al (2018) 21 ). However, no significant difference was observed with the WRC when comparing the two washing processes (Fig.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The washing solvents also showed a significant impact on the rheological parameters ( G ′ and G ′′), where washing with just water (CFS1) showed lower values as compared to a mixture of water and alcohol (CFS4). This indicates that a mixture of water and alcohol significantly decreases the insoluble components of both water and alcohol from the citrus fibres resulting in higher G ′ and G ′′ values as compared to washing with just water (similar behaviour was observed with the reduced pectin content via washing by Viuda-Martos et al (2012) 28 and Willemsen et al (2018) 21 ). However, no significant difference was observed with the WRC when comparing the two washing processes (Fig.…”
Section: Resultssupporting
confidence: 59%
“…Cellulose microfibres have been observed to exhibit gel-like viscoelastic properties ( G ′ > G ′′) as well as pseudoplastic and time-dependent thixotropic behaviour. 9,17–21 The highly entangled fibre network of cellulosic materials enables sufficient room for the uptake and retention of water, which provides these gel-like properties. 17 Research on the shear viscosity of citrus fibres has demonstrated the dependence of shear viscosity on the citrus fibre microstructure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant viscoelastic properties of the suspension were determined by oscillatory rheological analysis performed with a stress-controlled rheometer (MCR 302, Anton Paar, Graz, Austria). The analysis was based on the method of Willemsen et al [34] and was performed with the concentric cylinder system (2 mm gap), with rough surfaces designed and used by Willemsen et al [34]. After loading the suspension, a pre-shear was performed for 1 min at 10 s −1 , followed by 1 min of rest.…”
Section: Characterization Of the Functional Properties Of The Acid-unextractable Fractions In Suspension 271 Rheological Analysismentioning
confidence: 99%
“…In short, the rheological analysis (MCR 302, Anton Paar, Graz, Austria) consisted of a sequence of steps and made use of the rough concentric cylindric geometry designed by Willemsen et al (2018). When the suspension was loaded, a pre-shear (10 s -1 ) was applied for 1 min.…”
Section: Rheological Analysismentioning
confidence: 99%